Answer:
Perimeter of the rectangle = 8 x +4
Length of the rectangle = 12 units.
Step-by-step explanation:
Let the width of the rectangle as 'x' units.
So, length of the rectangle is 2 more than 3 x.
We can set up expression for length as 3 x+2.
Now, perimeter is sum of all side lengths of the rectangle.
So, perimeter = x+x+3 x+2 +3 x+2
Combine like terms,
Perimeter = 8 x+4
Now, it is given perimeter is 36cm
So,
8 x+4=36
Subtract both sides 4
8 x=32
Divide both sides by 8
x=4
So, width of the rectangle =4
Length =3(4) +2=14
Answer:
A = 3 ft, B = 7 ft, C = 4 ft, D = 5 ft, Surface Area = 96 ft^2
Step-by-step explanation:
<u>Step 1: Determine the sides</u>
A → 3 ft
B → 7 ft
C → 4 ft
D → 5 ft
<u>Step 2: Determine the surface area</u>
Area of the sides
![A= 4\ ft * 7\ ft = 28\ ft^2](https://tex.z-dn.net/?f=A%3D%204%5C%20ft%20%2A%207%5C%20ft%20%3D%2028%5C%20ft%5E2)
![A= 5\ ft * 7\ ft = 35\ ft^2](https://tex.z-dn.net/?f=A%3D%205%5C%20ft%20%2A%207%5C%20ft%20%3D%2035%5C%20ft%5E2)
![A= 3\ ft * 7\ ft = 21\ ft^2](https://tex.z-dn.net/?f=A%3D%203%5C%20ft%20%2A%207%5C%20ft%20%3D%2021%5C%20ft%5E2)
Area of the top and bottom triangles
![A= \frac{h\ *\ b}{2} = \frac{3\ ft\ *\ 4\ ft}{2} = \frac{12\ ft^2}{2} = 6\ ft^2 = 2(6\ ft^2) = 12\ ft^2](https://tex.z-dn.net/?f=A%3D%20%5Cfrac%7Bh%5C%20%2A%5C%20b%7D%7B2%7D%20%3D%20%5Cfrac%7B3%5C%20ft%5C%20%2A%5C%204%5C%20ft%7D%7B2%7D%20%3D%20%5Cfrac%7B12%5C%20ft%5E2%7D%7B2%7D%20%3D%206%5C%20ft%5E2%20%3D%202%286%5C%20ft%5E2%29%20%3D%2012%5C%20ft%5E2)
Total Area
![28\ ft^2 + 35\ ft^2 + 21\ ft^2 + 12\ ft^2](https://tex.z-dn.net/?f=28%5C%20ft%5E2%20%2B%2035%5C%20ft%5E2%20%2B%2021%5C%20ft%5E2%20%2B%2012%5C%20ft%5E2)
![96\ ft^2](https://tex.z-dn.net/?f=96%5C%20ft%5E2)
Answer: A = 3 ft, B = 7 ft, C = 4 ft, D = 5 ft, Surface Area = 96 ft^2
The algebraic representation of the statement is x + x² - yz = 0
<h3>What are algebraic expressions?</h3>
Algebraic expressions brings the idea of creating or expressing numbers using letters or alphabets without specifying their actual values.
From the information given , we have that;
- sum of x and it's square = x + x²
- Equal to y × z
Now, let's equate the expressions;
x + x² = y × z
x + x ² = yz
Let's make into quadratic form
x + x² - yz = 0
Thus, the algebraic representation of the statement is x + x² - yz = 0
Learn more about algebraic expressions here:
brainly.com/question/723406
#SPJ1
Answer:a scale facter is a scale of how much is one each side or corner and the shape
Step-by-step explanation:
His score was 40 each question was worth 5 points